Biopharmaceuticals: A review of their development and contribution to healthcare = Produtos biofarmacêuticos: Uma análise do seu desenvolvimento e contribuição para os cuidados de saúde - Liew, Kai Bin; Lee, Siew-Keah; Ming, Long Chiau; Helal Uddin, A.B.M.; Sarker, Zaidul Islam; Chew, Yik-Ling; Kee, Phei Er (ALIES, 2023)
Biopharmaceuticals play a crucial role in preventing, treating, and diagnosing a diverse range of diseases across various medical disciplines. The market for biopharmaceuticals has experienced significant growth, driven by tremendous demand, with their dynamic market potential believed to surpass that of conventional counterparts. This review provides insight into the manufacturing process of biopharmaceuticals, covering both upstream and downstream processing. Various types of biopharmaceutical products, such as monoclonal antibodies, enzymes, vaccines, stem cells, human growth hormones, cytokines, nucleic acids, and carbohydrates, are explored alongside their respective clinical applications. The review also addresses the challenges encountered in the development, formulation, and utilization of these biopharmaceuticals. In essence, this review contributes valuable knowledge to the understanding of the expansive field of biopharmaceuticals.